Effects of dam construction on the reproduction of the Yellow River carp (Cyprinus carpio) in lower reaches of the Yellow River, China - Ruan, Qiongyao; Li, Wenda; Zhang, Shanghong; Tang, Caihong; Hou, Jun (Frontiers in Environmental Science, 2023)
The construction of dams changes the natural flow of rivers, affects the integrity of river ecosystems, and causes a series of ecological and environmental problems, such as habitat fragmentation and fish resources reducing. This study takes a section of the Yellow River in China from the Xiaolangdi Dam to Gaocun as the research area. The Yellow River carp (Cyprinus carpio) is selected as an indicator species for its economic value. We build a habitat suitability model for the Yellow River carp coupled with a one-dimensional hydrodynamic model to simulate dynamic changes in the reproductive habitat suitability of the Yellow River carp before and after the construction of the Xiaolangdi Dam. We demonstrate the spatial distribution of the carp’s spawning reaches before and after the Xiaolangdi Dam construction and investigate its influence on the spawning activity and larval development of the species accordingly. The results apparently show that the construction and operation of the Xiaolangdi Dam delays time and decreases quality of the Yellow River carp reproduction, where especially the larval fish development is greatly affected by the dam. Furthermore, the habitat suitability of the spawning reaches slightly decreases, the extent of spawning reaches decreased by 16.23% and several spawning reaches are lost entirely. This study throws light on the response of the Yellow River carp to hydrological and physical changes before and after the construction of the Xiaolangdi Dam. Thus, it is a valuable reference for the ecological scheduling of discharges of the Xiaolangdi Dam.